Optimization of Mentorship Implementation to Enhance the Competence of Rotating Nurses in the NICU - Sitta Diani Fichara; Enie Novieastari; Krisna Yetti; Hening Pujasari; Sarvita Dewi (Indonesian Journal of Global Health Research, 2026)
X Hospital Jakarta Barat is a hospital that has implemented various competency development programs and continuing professional development initiatives for nurses. However, the implementation of mentorship as a clinical learning method has not yet run optimally and is not integrated across all units. A change is needed to optimize the implementation of mentorship activities by strengthening the roles and functions of nurse managers. Objective to optimize mentorship implementation in the NICU by strengthening nurse managers’ roles to enhance clinical competence and structured learning. This was a pilot project. The process started with problem identification, problem analysis, priority setting, preparation of a Plan of Action, implementation, and evaluation using Lewin’s change theory approach. The implementation of mentorship in the NICU showed an increase in clinical learning activities, with mentees beginning to independently carry out self-reflection without direct supervision. Mentors also felt assisted in monitoring mentee development through the provided guidelines and documentation formats. The head nurse and team leaders supported this program and were ready to facilitate its sustainability. Strengthening managerial roles improved mentorship implementation, increased mentee reflection, and enhanced mentor monitoring. With strong managerial support and clear documentation, mentorship can be sustainably integrated into institutional competency programs.